Evaluation of Pumice Source from Lubuk Basung Based on Magnetic Susceptibility Values - Febriwanti, Mutiara Kusuma; Hamdi, Hamdi; Fauzi, Ahmad; Syafriani, Syafriani (Department of Physics, Universitas Negeri Padang, 2024)
Lubuk Basung is one of the distribution areas of pyroclastic material from the Maninjau Caldera eruption that occurred 50,000 years ago and produced two different types of white pumice. The research purpose is to reveal whether the pumice samples taken from Lubuk Basung come from the same eruption or not based on susceptibility of magnetic scores. The susceptibility of magnetic scores can be measured by the Rock Magnetic Method using the Bartington Magnetic Susceptibility Meter Type B. From the magnetic susceptibility values obtained, normality test, homogeneity test, and mean similarity test of two different samples were conducted using IBM SPSS Statistics software. In the LBS 23-02 sample, a susceptibility of magnetic range of 41.9 x 10-8 m3/kg to 582.2 x 10-8 m3/kg was obtained, and the LBS 23-03 DB sample obtained a magnetic susceptibility value of 42.9 x 10-8 m3/kg to 535.5 x 10-8 m3/kg. From the normality, homogeneity, and mean similarity test, it is known that the LBS 23-02 and LBS 23-03 DB samples come from a population that is not distributed normally and not homogeneous, but an average comparison is obtained with a score of significance at 0.0426, which can be concluded that the two pumice samples found in Lubuk Basung come from the same eruption source, although each sample has different types and characteristics.